Subfunctionalization and neofunctionalization of vertebrate Lef/Tcf transcription factors - Klingel, Susanne; Holstein, Thomas W. (Developmental biology, 2012)
Invertebrates express a multitude of Wnt ligands and all Wnt/β-catenin signaling pathways converge to only one nuclear Lef/Tcf. In vertebrates, however, four distinct Lef/Tcfs, i.e. Tcf-1, Lef, Tcf-3, and Tcf-4 fulfill this function. At present, it is largely unknown to what extent the various Lef/Tcfs are functionally similar or diversified in vertebrates. In particular, it is not known which domains are responsible for the Tcf subtype specific functions. We investigated the conserved and non-conserved functions of the various Tcfs by using Xenopus laevis as a model organism and testing Tcfs from Hydra magnipapillata, Caenorhabditis elegans and Drosophila melanogaster. In order to identify domains relevant for the individual properties we created series of chimeric constructs consisting of parts of XTcf-3, XTcf-1 and HyTcf. Rescue experiments in Xenopus morphants revealed that the three invertebrate Tcfs tested compensated the loss of distinct Xenopus Tcfs: Drosophila Tcf (Pangolin) can substitute for the loss of XTcf-1, XTcf-3 and XTcf-4. By comparison, Caenorhabditis Tcf (Pop-1) and Hydra Tcf (HyTcf) can substitute for the loss of only XTcf-3 and XTcf-4, respectively. The domain, which is responsible for subtype specific functions is the regulatory CRD domain. A phylogenetic analysis separates Tcf-1/Lef-1 from the sister group Tcf-3/4 in the vertebrate lineage. We propose that the vertebrate specific diversification of Tcfs in vertebrates resulted in subfunctionalization of a Tcf that already united most of the Lef/Tcf functions.
Gesehen am 14.02.2017